Variabilidade genética de Pseudoplatystoma reticulatum do programa de melhoramento genético - Albuquerque, Daniele Menezes (2014)
The fish production in Brazil reached the 18th position in the world rank with 1,431,974,400,000 tons and an increase of 13.2% from 2010 to 2011 in South America occupying the 4th position in the fish production from the mining activity. Currently, several species are considered potential in Brazilian aquaculture, especially in the Midwest Region the cachara (Pseudoplatystoma reticulatum) production due to its high commercial value. They are large animals, fish-eating and migratory habits of long distance that are part of the top of food chain watershed. The cacharas present viable production characteristics in animal production with good growth rate and favorable feed conversion, reproductive biotechnologies in development with adaptation in various cropping systems, and already have a continuous supply of fingerlings in the producing regions. Because of these reasons, this species entered to the breeding program of aquaculture species coordinated by Embrapa having as nucleation agent the State University of Maringa - UEM. The breeding program of cachara started in 2008 with the formation of 72 families and had finished in 2013 under the original management molds. To monitor the genetic variability of these families that comprising the genetic breeding program were used molecular tools as DNA markers. The microsatellite markers can assist breeding programs in decision-making about the selection and direct new crosses in the same generation, thus increasing the efficiency and developing strategies for the genetic improvement of cachara families. Considering this problem, this study aims to characterize the genetic variability of five groups of Pseudoplatystoma reticulatum using microsatellite molecular markers from the genetic improvement program. Two hundred and eleven individuals from the F1 generation derived from 72 families were analyzed in a total of 62 alleles observed in the eight microsatellite loci polymorphic (Pcor01, Pcor05, Pcor08, Pcor10, Ppu01, Ppu04, Ppu09, Ppu10). There was an average allele frequency ranging between 0.0083 (Pcor08/85/110/118 - MS-II) and 0.500 (Pcor08/83 - MS-I). The heterozygosity observed average and inbreeding coefficient were 0.684; 0.643; 0.782; 0.728; 0.682; and 0.121; 0.168; 0.034; 0.061; 0,137, respectively for MT-I, MT-II , MS-I, MT-III and MS-II. It was observed deviation of Hardy-Weinberg equilibrium at most loci in five populations. Considering genetic differentiation, it was conclude that the five populations examined are different from one another, thus forming two groups made by three and two subpopulations, respectively.